Innovative Teaching-Learning Practices for Higher Education Institutes - Mumbai (India) - Acharya, Namrata; Johny, Jestin (SFIMAR Research Review, 2020)
The education sector has undergone a massive change right from the tradition methods of teaching that involved to learn through memorization and recitation techniques to the current modern pedagogies that induce critical thinking and problem-solving methods. The entire change in the system of teaching- learning has ensured that a student becomes rational thinker, knowledgeable, and self-sufficient. The creativity and innovation in the teaching pedagogy has ensured that both students and teachers benefit and have changed the landscape of the education with more empowered individuals, stronger governance, and development of human capital in the country. The current disruption in the education sector is due to the Covid-19 pandemic, which has further opened gates to creativity and innovation increasing the use of online platforms and change in teaching-learning pedagogy for both teachers and students. The paper focuses on secondary data and discussion with faculties of other institutes. This research paper focusses on studying the different teaching-learning practices proposed by universities and technical bodies and adopted by higher educational institutes in the Mumbai district. This research paper focusses on the innovative teaching-learning practices at the institutes in Mumbai District.